ORIGIN OF THE CREATIVE SCHOOL OF MANAGEMENT: RETROSPECTIVE ANALYSIS - Litovchenko, Bogdan (Journal of European Economy, 2017)
The emergence and development of creative economy in the contemporary global society poses challenges to the theory and practice of classical views on management. The aim of the study is to identify the main principles for creative management for modern organizations. The tasks of analysis of characteristics of the creative organization in historical retrospective are based on the views of classical theory and practice of management are solving and establishment of creative management in global environment as a tool of effectiveness of building a new socio-economic system with purpose of achieving this goal. Creative management is considered in the context of synergy of creativity, innovation and ethical business.